Blood vessel anastomosis is spatially regulated by Flt1 during angiogenesis - Nesmith, Jessica E. (Development, 2017)
Blood vessel formation is essential for vertebrate development and is primarily achieved by angiogenesis – endothelial cell sprouting from pre-existing vessels. Vessel networks expand when sprouts form new connections, a process whose regulation is poorly understood. Here, we show that vessel anastomosis is spatially regulated by Flt1 (VEGFR1), a VEGFA receptor that acts as a decoy receptor. In vivo, expanding vessel networks favor interactions with Flt1 mutant mouse endothelial cells. Live imaging in human endothelial cells in vitro revealed that stable connections are preceded by transient contacts from extending sprouts, suggesting sampling of potential target sites, and lowered Flt1 levels reduced transient contacts and increased VEGFA signaling. Endothelial cells at target sites with reduced Flt1 and/or elevated protrusive activity were more likely to form stable connections with incoming sprouts. Target cells with reduced membrane-localized Flt1 (mFlt1), but not soluble Flt1, recapitulated the bias towards stable connections, suggesting that relative mFlt1 expression spatially influences the selection of stable connections. Thus, sprout anastomosis parameters are regulated by VEGFA signaling, and stable connections are spatially regulated by endothelial cell-intrinsic modulation of mFlt1, suggesting new ways to manipulate vessel network formation.